Developing Descriptive Writing Materials by Using Padlet Application in the Tenth Grade Students at SMK AL Washliyah 3 Medan - Rini Surya Ningsih; Ahmad Laut Hasibuan; Asnawi Asnawi; Yulia Arfanti (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research is to develop descriptive writing material, determine the validation of descriptive writing material and to increase the effectiveness of descriptive writing material by using the padlet application in teaching writing for class X students at SMK AL Washliyah 3 Medan. The research was carried out using the Development Research method, and the evaluator was an English subject teacher, and the subjects were class X students. Pre-test and post-test were carried out to determine the effectiveness of the results. The pre-test results obtained an average score of 70.15% in the satisfactory category; The post-test results show an average score of 82.15% in the very good category. The process of developing teaching materials includes three aspects of assessment: 1) development of descriptive writing materials; 2) validation of descriptive writing material and; 3) effectiveness of descriptive writing materials. Material expert validation includes content with an average score of 3.15% and percentages 4.35% in the superior category. Feasibility of presenting teaching materials has an average score of 5.67% in the superior category, and linguistic elements have an average score of 4.25% in the superior category. The conclusion shows that the design for developing descriptive text teaching materials using a scientific approach in English subjects is very effective.